Generation of cardio-protective antibodies after pneumococcal polysaccharide vaccine: Early results from a randomised controlled trial. (April 2022) - Ren, Shu; Hansbro, Philip M.; Srikusalanukul, Wichat; Horvat, Jay C.; Hunter, Tegan; Brown, Alexandra C.; Peel, Roseanne; Faulkner, Jack; Evans, Tiffany-Jane; Li, Shu Chuen; Newby, David; Hure, Alexis; et al.
Abstract: Background and aims: Observational studies have demonstrated that the pneumococcal polysaccharide vaccine (PPV) is associated with reduced risk of cardiovascular events. This may be mediated through IgM antibodies to OxLDL, which have previously been associated with cardioprotective effects. The Australian Study for the Prevention through Immunisation of Cardiovascular Events (AUSPICE) is a double-blind, randomised controlled trial (RCT) of PPV in preventing ischaemic events. Participants received PPV or placebo once at baseline and are being followed-up for incident fatal and non-fatal myocardial infarction or stroke over 6 years. Methods: A subgroup of participants at one centre (Canberra; n = 1, 001) were evaluated at 1 month and 2 years post immunisation for changes in surrogate markers of atherosclerosis, as pre-specified secondary outcomes: high-sensitive C-reactive protein (CRP), pulse wave velocity (PWV), and carotid intima-media thickness (CIMT). In addition, 100 participants were randomly selected in each of the intervention and control groups for measurement of anti-pneumococcal antibodies (IgG, IgG2, IgM) as well as anti -OxLDL antibodies (IgG and IgM to CuOxLDL, MDA-LDL, and PC-KLH). Results: Concentrations of anti-pneumococcal IgG and IgG2 increased and remained high at 2 years in the PPV group compared to the placebo group, while IgM increased and then declined, but remained detectable, at 2 years. There were statistically significant increases in all anti -OxLDL IgM antibodies at 1 month, which were no longer detectable at 2 years; there was no increase in anti -OxLDL IgG antibodies. There were no significant changes in CRP, PWV or CIMT between the treatment groups at the 2-year follow-up. Conclusions: PPV engenders a long-lasting increase in anti-pneumococcal IgG, and to a lesser extent, IgM titres, as well as a transient increase in anti -OxLDL IgM antibodies. However, there were no detectable changes in surrogate markers of atherosclerosis at the 2-year follow-up. Long-term, prospective follow-up of clinical outcomes is continuing to assess if PPV reduces CVD events. Graphical abstract: Image 1 Highlights: In mice, immunisation against Pneumococcus elicits anti -oxLDL antibodies which inhibit atherosclerotic plaque growth We provide the first RCT evidence in humans that the pneumococcal polysaccharide vaccine elicits the same protective anti -oxLDL antibodies at 1 month. By 2 years, these antibodies have returned to baseline levels and do not have any measurable effect on surrogate markers of CVD, including CRP, pulse wave velocity or carotid intima-media thickness